Effect of Specific Resistance Training in the Physical Efficiency and Performance Endurance for Some Defensive and Offensive Movements in Handball - هديل عامر أ.م.د. حردان عزيز سلمان أ.د. وداد كاظم الزهيري (الرياضة المعاصرة, 2018)
The aim of the research is to prepare specific resistance training in order to improve the physical efficiency and performance endurance for defensive and offensive movements of Al-Jaish players club of handball, and to know the effect of these exercises in the physical efficiency and performance endurance of some defensive and offensive movements for the research sample. The research problem is that the performance of the players and it seems obvious in the final minutes of the game, showing signs of loss of concentration and accuracy and the inability of the player to continue a good level of defense and attack and he can’t play the required role of tactical plans And the duties assigned to him in the court as well as a lot of mistakes in the court, which is one of the reasons for the decline in the level of physical efficiency of players. The aim of this study is to prepare a specific resistance training to improve the physical efficiency and technical endurance performance and to know the effect of specific resistance training in the development of physical efficiency and performance endurance of some of the defensive and offensive movements for Al-Jaish players of handball.The hypothesis of research, there are statistically significant differences between the results of the pre and post-tests in the physical efficiency and performance endurance of some defensive and offensive movements in the research sample. The researchers used the experimental method to suit the nature of the research with sample of (14) players from the Al-Jaish club of Handball.